2009
DOI: 10.1136/thx.2008.104133
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial to mesenchymal transition (EMT) and airway remodelling after human lung transplantation

Abstract: Background: Aberrant epithelial repair is a key event in the airway remodelling which characterises obliterative bronchiolitis (OB) in the transplanted lung. The potential for airway epithelium from lung transplant recipients to undergo epithelial to mesenchymal cell transition (EMT) was assessed in culture and in vivo in lung allograft tissue. Methods: Change in epithelial and mesenchymal marker expression was assessed after stimulation with transforming growth factor b 1 (TGF-b 1 ) alone or in combination wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(123 citation statements)
references
References 30 publications
8
113
0
1
Order By: Relevance
“…Lung fibroblasts can be derived from fibroblasts in situ or from the recruitment of circulating precursors in the site of inflammation. Recent studies suggest that EMT is implicated during the development of BO [29,30,155,156], as has been demonstrated for chronic kidney rejection [157][158][159][160]. A study with biopsies and ex vivo cultures from lung transplant recipients showed that BEC expressed S100A4 [30].…”
Section: Emt and Bo Following Lung Transplantationmentioning
confidence: 99%
See 3 more Smart Citations
“…Lung fibroblasts can be derived from fibroblasts in situ or from the recruitment of circulating precursors in the site of inflammation. Recent studies suggest that EMT is implicated during the development of BO [29,30,155,156], as has been demonstrated for chronic kidney rejection [157][158][159][160]. A study with biopsies and ex vivo cultures from lung transplant recipients showed that BEC expressed S100A4 [30].…”
Section: Emt and Bo Following Lung Transplantationmentioning
confidence: 99%
“…BORTHWICK et al [29] reported that BEC isolated from BO patients could undergo EMT, characterised by a decrease in the expression of E-cadherin and an increase in the expression of vimentin and a-SMA. Cotreatment with TGF-b and TNF-a accentuates the mesenchymal phenotype.…”
Section: Emt and Bo Following Lung Transplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…While in vitro models of OB have utility in showing how individual populations, such as bronchial epithelial cells, mesenchymal stromal cells, and airway smooth muscle cells, may contribute to disease (95)(96)(97)(98), animal models can provide a window into the events from transplant to the final fibrotic obliteration of small airways and is key to investigating the pathogenesis of OB and conducting preclinical studies of potential therapeutic interventions. Utilized models of post-lung-transplant OB are based on allogeneic lung tissue transplantation with a goal of reproducing fibrotic airway remodeling.…”
Section: Cladmentioning
confidence: 99%